Gentamicin Does Not Chelate Calcium - Kohlhepp, Sue J. (1982)
The influence of increasing gentamicin concentrations on ionized calcium concentration was determined in pH-controlled, phosphate-buffered saline and normal human serum with an ion-specific calcium electrode. No evidence of calcium chelation was found.